A paper Caliphate: understanding the Islamic State through its documents - Diogo Bercito (Malala)
The Islamic State is a terror organization that distinguishes itself from other similar groups by the establishment of a bureaucratic structure that projects the image of a state. This essay investigates documents produced in Iraq under the banner of the caliphate. These documents reveal an administration that enforces itself over a large territory. Their analysis points to a particular view of government presented as Islamic, which this investigation compares with precedents set throughout Islamic history, while traces of the modern conception of a state are found to be salient.